Capture of time-loss overuse soccer injuries in the National Collegiate Athletic Association's injury surveillance system, 2005-2006 through 2007-2008 - Roos, K.; Kucera, K. L.; Golightly, Y.; Myers, J. B.; Rosamond, W.; Marshall, S. W. (Journal of Athletic Training, 2018)
Context: Overuse injuries are reported to account for nearly 50% of sports injuries and, due to their progressive nature and the uncertainty regarding date of onset, are difficult to define and categorize. Comparing the capture rates of overuse injuries between injury-surveillance systems and medical records can clarify completeness and determinants of how overuse injuries are represented in injury-surveillance data.